Natural Social Training and Targeted Forms of Influence and Their Impact on Development of Soft Competences among Team Leaders: A Comparative Analysis - Marzena STASZKIEWICZ; Wojciech KOWALIK (Communications of International Proceedings, 2021)
The article is an attempt to present the role of natural social training and targeted forms of influence on the level of soft competences of lower rank managers. Considering the increasing interest in the issues of development of psychosocial competences among managers, the field of potential ways of shaping these competences has become a significant issue. In this context, on the one hand, emphasis is placed on the enormous role of the so-called natural social training; on the other hand, there is a visible increase in significance of methods employing targeted influence on the level of psychological and social competences. The research carried out was aimed at determining the strength of the correlation between intensity of natural and laboratory social training and the level of soft competences displayed by the managers examined. The main goal of the study was to find out whether intensive natural training as well as participation in activity-based training would result in a higher level of soft competences compared to those achieved by people less involved in both forms of training. A set of questionnaires was used: The Bochum Inventory of Personal Work Features and a survey concerning the activity of managers in development of their soft competences. 101 respondents participated in the study. The summary of results obtained also indicates the important role of universities in shaping and developing of psychosocial competences.
Keywords: Managerial Competences; Soft Competences; Social Competences; Development Of Soft Competences; Natural Social Training; Team Leaders